Weed management on direct-seeded rice system - a review - Hossain, MM; Begum, M; Rahman, MM; Akanda, MM (Progressive Agriculture, 2016)
In direct seeded rice (DSR) cultivation systems, rice and weed seedlings emerge simultaneously and there is no standing water to suppress weed emergence and growth at crop emergence. For this reason, weeds are considered one of the major biological constraints in DSR and cause a substantial rice yield loss. Weeds are mainly controlled using herbicides or manually. However, manual weeding is becoming less effective because of labor crisis at critical times and increased labor costs. Herbicides are replacing manual weeding as they are easy to use but there are concerns about the sole use of herbicides, such as evolution of resistance in weeds, shifts in weed populations, cost of weed management to farmers and concerns about the environment. There is a need to integrate different weed management strategies to achieve effective and sustainable weed control in DSR systems. This paper describes different approaches, including preventive and cultural approaches, to manage weeds in DSR culture systems. Progressive Agriculture 27 (1): 1-8, 2016